Estrogen Receptors, Progesterone Receptors and their Correlation with respect to HER-2/neu Status, Histological Grade, Size of Lesion, Lymph node Metastasis, Lymphovascular Involvement and Age in Breast Cancer patients in a hospital in north India - Nabi, Mushood G.; Ahangar, Andleeb; Kaneez, Subiya (Asian Journal of Medical Sciences, 2016)
Background: Breast cancer is the second most common cancer overall (1.4 million cases, 10.9%) and ranks 5th as cause of death (458,000. 6.1%).The present study was aimed to find the pattern of expression of ER, PR, HER-2/neu and to correlate ER, PR status with respect to various clinicopathlogical factors like HER-2/neu over expression, histological grade, tumor size, lymphnode metastasis, lymphovascular invasion and age of the patient. Materials and Methods: Data from 139 patients was collected and correlation of ER, PR status with various clinicopathological factors was analysed. Results: Mean age at diagnosis was 48.5 years, 56.8% cases being ?50years of age. Tumor size ranged from 1 to 12 cm. Most lesions (57.5%) were>2 to 5 cm in size. The predominant morphology was Infiltrating Duct carcinoma-NOS (90.6%). Majority of cases presented as grade II(46.7%) lesions and lymph node involvement was seen in 66.9%. 49.6% cases were ER+, 49.6% cases were PR+, and HER-2/neu was positive (3+) in 15.8% cases. Older patients were mostly ER+PR+. Low grade tumors were mostly ER+PR+ as compared to high grade tumors. HER-2/neu status revealed an inverse association with hormone receptor positivity. No correlation was found between hormone receptor positivity and lymph node metastasis. Lymphovascular involvement was noted more in hormone negative ER-PR- tumors. Conclusion: ER and PR expression in our patients was found to be comparable to the studies done in Indian subcontinent, but lower than studies done in west, but triple negative breast cancer prevalence was relatively higher in our study (34.5%). Asian Journal of Medical Sciences Vol. 7(3) 2016 28-34